Pengaruh Kompetensi Pedagogik Guru dan Lingkungan Teman Sebaya (Peer Group) terhadap Prestasi Belajar Siswa Keluarga Miskin Kelas X dan XI SMA Negeri 1 Surakarta - Pelangi Atha; Kristiani Kristiani; Budi Wahyono (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2021)
The aims of this research are to determine: 1) the influence of teacher’s pedagogic competence toward the learning achievement of students of poor family of Class X and XI in SMA Negeri 1 Surakarta, 2) the influence of peer group environment toward the learning achievement of students of poor family of Class X and XI in SMA Negeri 1 Surakarta, and 3) the simultaneous influence of the teacher’s pedagogic competence and peer group environment toward the learning achievement of students of poor family of Class X and XI in SMA Negeri 1 Surakarta. This research is a quantitative research. The population of the research was the poor students of Class X and XI in SMA Negeri 1 Surakarta in the academic year of 2017/2018. The sampling technique used was Census Sampling. The number of samples was 105 respondents. The data collection methods used were interview, questionnaire, and documentation. The data analysis technique used was multiple linear regression. The result of the research shows that the equity of the multiple regression is Y= 24.760 + 0.605 X1 + 0.905 X2. The regression coefficient is positive which means that the teacher’s pedagogic competence is positively and significantly influential toward the learning achievement of the students of poor family and peer group environment is positively and significantly influential toward the learning achievement of the students of poor family. It means that the better the teacher’s pedagogic competence is, the higher the students’ learning achievement will be and the higher the influence of peer group environment is, the higher the students’ learning achievement will be. Based on the result of the research, it can be concluded that: 1) the teacher’s pedagogic competence is positively and significantly influential toward the learning achievement of the students of poor family which is shown by the probability value of <0.05 (0.000<0.05), 2) peer group environment is positively and significantly influential toward the learning achievement of the students of poor family which is shown by the probability value of <0.05 (0.000<0.05), 3) teacher’s pedagogic competence and peer group 2 environment simultaneously is positively and significantly influential toward the learning achievement of the students of poor family which is shown by the probability value of <0.05 (0.000<0.05) and R square value of 58.9%. It is shown that 58.9% of the learning achievement of the students of poor family is influenced by the teacher’s pedagogic competence and peer group environment, while the rest which is 41.1% is influenced by other factors not mentioned in this research